2018
DOI: 10.1021/acs.energyfuels.8b00722
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Effect of Gasoline on Fuel Economy and Emissions

Abstract: In the paper, fuel economy and emissions of a port-fuel-injection engine fueled with four gasoline were experimentally investigated to verify the validity and universality of the conclusions from the previous experiment conducted in a gasoline-direct-injection engine. On the basis of the previous results, which showed that aromatics and short-chain alkanes were beneficial to improving fuel economy and that oxygenated fuels could reduce emissions to some extent, commercial gasoline with a research number of 92 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…For the hot-start LA92, NO x emissions for E78 were lower at a statistically significant level than both E10 fuels. Previous studies have shown NO x reductions with higher ethanol blends. , Other studies have also shown higher NO x with increasing aromatics, consistent with the differences seen between E10 and E10HA . The lower NO x emissions for the higher ethanol fuels could be due to the lower adiabatic temperature for oxygenated fuels.…”
Section: Resultssupporting
confidence: 69%
“…For the hot-start LA92, NO x emissions for E78 were lower at a statistically significant level than both E10 fuels. Previous studies have shown NO x reductions with higher ethanol blends. , Other studies have also shown higher NO x with increasing aromatics, consistent with the differences seen between E10 and E10HA . The lower NO x emissions for the higher ethanol fuels could be due to the lower adiabatic temperature for oxygenated fuels.…”
Section: Resultssupporting
confidence: 69%
“…With development in the world, energy and environmental issues cannot be ignored. In order to reduce emissions and improve energy efficiency to meet stricter emission regulations, new combustion modes (HCCI, PCCI, RCCI, LTC, etc.) and comprehensive fuels have been adopted. , Co-optimization of fuels and engines makes it possible to further improve engine performance.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental concern over the effects of exhaust emissions from internal combustion engines (ICEs) drives emission standards to be set at lower tolerance levels, while oil shortages trigger renewed interest in raising the fuel economy of gasoline engines. , To upgrade the gasoline thermal efficiency, many advanced ICE technologies, involving combustion concepts, engine hardware, fuel injection pressure, engine control strategy, turbo compound, lean boosting, and other gleaning technologies, were developed in recent years. Researchers have also paid more attention to fuel improvement technologies, which promote various oxygenated fuels and biomass fuels as alternatives or additives to fuels. Because of the advantage of oxygen-borne characteristics in molecules, incomplete burning can largely be relieved, raising combustion efficiency and lowering exhaust emissions. Owing to raw material production costs, transition costs, storage capacity, and regional disparity, however, most alternative fuels have restricted practical applications …”
Section: Introductionmentioning
confidence: 99%
“…Gasoline, as the main fuel for gasoline cars, contains different kinds of straight-chain paraffins, isoparaffins, cycloparaffins, aromatics, olefins, and components with oxygen. Hence, many studies have focused on the effects of gasoline components on the performance and emissions of gasoline engines in recent decades. Based on the tests over a wide range of engine operating conditions (various speeds and throttle positions), Machado et al found that n -heptane improved the combustion efficiency and overall efficiency of engines, while reducing carbon monoxide (CO) and total hydrocarbon (THC) emissions, without significantly increasing carbon dioxide (CO 2 ) emissions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation